Principles of Selection of Materials on the Problem Method of Teaching Physics in Secondary Schools (Texas Journal of Multidisciplinary Studies, 2022)
The article presents the ways of using the problematic situation method in teaching physics, choosing the materials that support the problematic teaching method. In order for students to deeply master physics, the choice of separate materials for solving more issues and performing laboratories gives good results. The article presents a wide range of methods of using problematic teaching techniques in teaching physics and found its confirmation in the results obtained.